6, 13-pentacenequinone/zinc oxide nanocomposites for organic dye degradation. (2022) - Jawale, Vivekanand; Al-fahdawi, Aeed; Salve, Sunanda; Pandit, Shivaji; Dawange, Ganesh; Gugale, Gulab; Chaskar, Manohar; Hammiche, Dalila; Arbuj, Sudhir; Pandit, Vikram
Abstract: The organic semiconductor photocatalyst 6, 13-Pentacenequinone (PQ) and inorganic photocatalyst ZnO were synthesised independently. PQ was synthesised by previously reported solution method and nanostructured ZnO by sol–gel synthesis method. Keeping in mind the previous photocatalyst composite systems of PQ, PQ/ZnO nanocomposite system prepared with different weight ratios by simple wet impregnation method. The as synthesised organo-inorganic nanocomposite catalyst system was characterized with various spectroscopic methods. XRD confirms the monoclinic and hexagonal wurtzite phase of PQ and ZnO, respectively. FE-SEM showed the sheet/plate like morphology of PQ, whereas the composite material depicts the formation of homogeneous layer of ZnO on PQ surface in all three compositions. Photocatalytic activity of these semiconductor nanosystems was studied and compared with PQ/TiO2 composite systems for degradation of methylene blue (MB) dye under sunlight. As compared to individual, the coupled organo-inorganic catalyst showed higher photocatalytic MB degradation. The PQ/ZnO nanocomposite having 0.5 wt% PQ showed highest MB degradation.